2005
DOI: 10.1590/s1020-49892005000100001
|View full text |Cite
|
Sign up to set email alerts
|

Visual inspection with acetic acid for cervical cancer screening outside of low-resource settings

Abstract: VIA is useful for detection of precursor lesions of cervical cancer not only in low-resource settings but also in well-equipped health centers and cancer centers. In these non-low-resource settings, VIA has a positive predictive value comparable to the conventional Pap smear, but it is more likely to achieve earlier diagnosis, follow-up, and treatment than cytology-based screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 16 publications
4
47
1
Order By: Relevance
“…The 7% rate of positive VIA tests in the present study is similar to the rates reported for Peru (6.8%) [20] and Colombia (7.4%) [21], but lower than the rates found in Mongolia (12.6%) [22], Kenya (13.2%) [19], Ghana (13.2%) [13], and Thailand (13.3%) [12]. Whether this represents a difference in the prevalence of CIN or is related to the performance of the test cannot be determined without histology.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The 7% rate of positive VIA tests in the present study is similar to the rates reported for Peru (6.8%) [20] and Colombia (7.4%) [21], but lower than the rates found in Mongolia (12.6%) [22], Kenya (13.2%) [19], Ghana (13.2%) [13], and Thailand (13.3%) [12]. Whether this represents a difference in the prevalence of CIN or is related to the performance of the test cannot be determined without histology.…”
Section: Discussionsupporting
confidence: 90%
“…A study from Guatemala [23] noted only a small number of refusals for VIA (2%) or cryotherapy (1%). A Peruvian study [20] demonstrated that 40% of women considered ineligible for cryotherapy at the time of VIA did not attend for further investigation and treatment, indicating the importance of immediate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to read the cervical smears at public sector laboratory is limited (Fonn, 2003). In developing countries, because of lack of the trained cyto-technicians, there is often a long interval of 1-3 months between the Pap screening and when the test result is available (Jeronimo et al, 2005). This is further supported by the findings of the study that was conducted by Moodley et al (2006) which revealed that long cytology turnaround time is attributed to poorly functioning administrative and transportation systems.…”
Section: Shortage Of Health Care Workersmentioning
confidence: 94%
“…In developing countries, because of the lack of trained cytotechnologists and cytology laboratories, there is often a long interval (1-3 months) between the Pap screenings and when the test result is available. VIA has the advantage of requiring only low-technology equipment and the result is available immediately (Jeronimo et al, 2005). Therefore, the treatment of abnormal lesions can be done during the same consultation.…”
Section: Effective Screening Testsmentioning
confidence: 99%
“…In a study conducted by Sankaranarayanan et al [7] in 1998, VIA was found to have a positive predictive value (PPV) of 90% versus the Pap smear (86.2%). Jeronima et al [1] conducted a study in the year 2005, which found VIA to be more effective in the detection of cancerous lesions than the Pap smear, with a greater PPV, 83%, versus the Pap smear (63%). In a study conducted in the year 2012 [3] , VIA had a sensitivity of 77% in the detection of cancerous lesions, with a specificity of 86%.…”
Section: Discussionmentioning
confidence: 99%